Frequency of Corrected QT Interval in Patients With Cirrhosis - Mashhood Ali, Arslan Shahzad, Inayatullah Khan Adil, Shan Alam, Haseeb Noor,Asif Imran ,Naveed Ganito (Journal of Rawalpindi Medical College, 2016)
Background:. To assess the frequency of QTc prolongation in patients with liver cirrhosis and to observe its association with the severity of cirrhosis. Methods: This cross-sectional observational study included 189 diagnosed cases of liver cirrhosis who were consecutively recruited and categorized according to Child-Pugh class, to rate the severity. QTc interval prolongation was observed, and its association with Child-Pugh class scores (severity of Liver Cirrhosis) was assessed using Chi-square test keeping p-value less than 0.05 as statistically significant. Results: The mean age of the participants was 51.25 ±14.34, and gender distribution showed that96 (51%) were male and 93 (49%) were female. Q-Tc interval was normal in 99 (52%) patients and was prolonged in 90 (48%) patients. The QT-c interval prolongation was significantly associated with severity of liver cirrhosis. (p-value =0.000) Conclusion: QTc interval was prolonged in almost half of the patients and the frequency of prolonged QTc was directly proportional to the severity of the hepatic cirrhosis according to Child-Pugh criteria